Silent Struggles: Addressing Psychiatrist’s Grief After Patient Suicide - Nur Iwana, Abdul Taib; MUHAMMAD HANIF, ABD LATIF; NURAZAH, ISMAIL; JOHARI, KHAMIS; RAVIVARMA, RAO PANIRSELVAM; TUTI IRYANI, MOHD DAUD; ABDUL HAKEM, ZAHARI (2024)
The loss of a patient to suicide is profoundly impactful for any psychiatrist. Despite this, psychiatrists often do not receive adequate support in coping with such a loss. This article aims to review the experiences of psychiatrists dealing with the loss of a patient who died by suicide, examine its impact on their clinical practice, and identify potential support measures that can be implemented. A comprehensive literature review focused on the experiences of psychiatrists, clinicians, and other mental health professionals who have lost patients to suicide. The selected articles were either in English or had English translations and addressed experiences, impacts, or recommended postvention protocols for these healthcare providers. Out of 62 reviewed articles, the majority emphasised that losing a patient to suicide is a common and profound experience for psychiatrists worldwide. Many psychiatrists face this loss at least once in their careers, with some encountering it multiple times. Studies from various countries, including the United States, Thailand, and Canada, reveal that a significant percentage of psychiatrists have experienced patient suicide. This loss frequently occurs early in their careers, sometimes during postgraduate training, where its impact is particularly severe. Globally, there are limited postvention protocols and guidelines to manage the complex consequences of a patient’s suicide. Barriers to seeking support for psychiatrists who have survived such incidents include concerns about confidentiality, disenfranchised grief, negative reactions from colleagues, and the stigma associated with suicide. The review highlights psychiatrists’ silent grief and inadequate support after a patient’s suicide. The impact is influenced by their relationship with the patient, suicide circumstances, and coping mechanisms. In Malaysia, the grief experienced by psychiatrists following a patient’s suicide remains underexplored despite its significance. Developing local guidelines or postvention protocols tailored to the sociocultural context in Malaysia is essential to support psychiatrist-survivors effectively.